An Azanian Trio : Three East African Arabic Historical Documents - Sicard, Sigvard von,; Ritchie, James McL., (Middle East and Islamic Studies E-Books Online, Collection 2019, ISBN: 9789004386341., 2019)
This work consists of the translation and annotation of three East African Arabic / Swahili manuscripts together with the original texts. They cover aspects of the history of the coast from the early Himyaritic period up to the beginning of the 20th century. By the use of earlier, in some cases hitherto unused Arabic sources, the authors of the texts have contributed to a fuller picture of the East African coastal history. The texts relate directly to works on East African coastal history that have appeared since the latter part of the 19th century. They are presented against the background of general Arabic and Islamic history. The annotations indicate, and some case stress, significant hints and references to matters that need to be borne in mind, along with archeological and other evidences.